Proactividad administrativa y su incidencia en el desempeño laboral en las secretarias del GAD Parroquial Rural La Unión en el período -2022 - Montoya Peña, Ginger Valeria (2022)
The present research project on a vital aspect in the performance and administrative management of any company or organization, that is, the proactivity of employees as an essential component in the efficiency and work performance of their functions. For the La Unión Parish GAD, proactivity in its officials, especially the Secretaries, is paramount, since this attitude helps to improve performance in their activities and therefore to achieve the goals set by the company. The secretaries are, in the first instance, the image and entrance door in the departments or offices where they work, as well as contact with citizens. This study is carried out with the purpose of analyzing the incidence of administrative proactivity in work performance in the secretaries of the La Unión rural parish GAD in the period 2021-2022. The research is approached by compiling the needs that the Secretaries have to improve their environment. and job performance through the survey technique that has allowed us to find shortcomings and weaknesses of why there is no proactive behavior within the Institution. The results showed that the main cause lies in the motivation that is not properly managed by the Institution, so an action plan was proposed to strengthen the proactivity of the secretarial staff and thus improve their work performance. For all that this project contributes, its viability is feasible, directly benefiting the Secretaries through the heads and authorities who will be able to have more efficient employees in their administrative and management functions.